A relação entre avós idosos(as) e netos(as) por meio das tecnologias de informação e comunicação. - Torres, Karine de Andrade (2020)
The increase in the life expectancy of the human being results in the greater possibility of coexistence among the generations of a family. The changes that have been taking place in the structure and dynamics of this system make up a context in which grandparents have assumed increasingly important roles in family relationships. Increasingly these relationships have been established through cyberspace which is considered as a virtual universe formed by information that circulates and / or is stored on all computers connected in network, especially the World Wide Web. This qualitative research aimed to investigate how the New Information and Communication Technologies (NICTs) affect the relationship between grandparents and grandchildren. Specifically, we investigated the relationship that the elderly have established with NICTs, as grandparents and grandchildren perceive and evaluate the relationship established between them through the virtual world, as well as the meanings attributed to what is to be grandfather / grandmother and grandchild / granddaughter in this technological context. Data were collected through semi-structured interviews with 12 elderly grandmothers and 12 adult grandchildren of both sexes. The interviews were recorded, transcribed and then analyzed according to the content analysis method. The findings showed that most of the grandparents interviewed pointed out as benefits the speed and immediacy with which they communicate with their grandchildren through technology, indicating a sense of belonging to the family and the age group of the grandchildren. It was verified that great part of the grandparents had the initial contact with the NICTs through grandchildren and / or relatives. The findings also indicated that the interest in NICTs seems to be fundamentally of a social and family character, being related to the improvement of the quality of life. The results also pointed out the difficulties of the elderly in the use of technological tools. Among them we can mention the writing /typing, as well as the understanding of the functionality of the mobile apps. One fact that caught our attention in the interviews, both grandparents and grandchildren, was the report of physical problems caused by the excessive use of technology such as sight and tendinitis and /or muscle pain. The grandparents added that the affection, affinity and love between them and their grandchildren are feelings that are strengthened through the internet. In turn, most of the grandchildren interviewed revealed that the use of technology was directed towards the objective of functionality and practicality for communication, but it was quite evident the pleasure of being connected and relating to their grandparents. It is concluded that communication technologies have taken an important place in this relationship because they aren`t only used to shorten distances, communication technologies are also promoters of health and well-being, enabling the strengthening of affective bonds and the relations of care between the generations.